المرأة العراقية بين التعليم والسياسة في العهد الملكي (1921-1958) (دراسة تاريخية) - عطية, بنين عوده عبد (Tasnim International Journal for Human, Social and Legal Sciences, 2025)
The research aims to shed light on the transformations that Iraqi women witnessed during the royal era (1021-1958 AD), by focusing on two main axes: education and political participation. The research begins by reviewing the status of women during the Ottoman era. Women suffered from social and cultural marginalization, as their role was limited to family life and work within the home only, and they were deprived of education and political participation. However, during the royal era, the status of Iraqi women changed completely through the emergence of official and popular efforts to educate girls, especially in major cities, and the emergence of feminist voices through the press, which played a major role in supporting and backing Iraqi women and their rights in life, equal to men. Several feminist associations also emerged that defended women’s social and cultural issues, and this played a major role in developing awareness among Iraqi women of their rights and position in society. This research also addressed the growth of political awareness among Iraqi women, as they began to participate in public activities such as demonstrations, protests, and sit-ins, such as their participation in the January Uprising (1948 AD) and the uprising of 1952 AD. This participation was not random, but rather came as a result of an intellectual and cultural accumulation contributed to by schools, feminist journalism, and also associations founded by Iraqi women.